Problems of legal provision of investment activity by using water and forest resources (Journal of actual problems of jurisprudence, 2018)
This article discusses the issues of legal regulation of investment activity in the use of water and forest resources. Problems of legal provision of attracting investment in the sector. Environmental issues, including sustainable use of water and forest resources and forest renewability. The problems of the introduction or improvement of the investment, environmental, land, water legislation, national legislation in the field of environmental protection, transport, construction, that could create powerful market incentives and encourage investment and efficient use of water and forest resourcesKey words: legal regulation, water resources, forest resources environmental protection, investment.